Optimization of condensation reaction time between vanillin and p-nitroacetophenone in acid catalysts - Indyah Sulistyo Arty Sulistyo Arty; Dini Rohmawati (Faculty of Mathematics and Natural Science, Universitas Negeri Yogyakarta, 2014)
This study was an experimental study aimed to obtain the optimal time in the synthesis of chalcone compounds through cross aldol condensation reaction. The starting materials used were vanillin, p-nitroacetophenone, and acid catalyst. The study began by reacting vanillin and p-nitroacetophenone in HCl catalyst and the flow of nitrogen. The optimalization of reaction time was done in some variation of time, 3 hours, 5 hours and 7 hours. The reaction products were recrystallized with solvents mixture aquades: ethanol (1:1). Recrystallization product then checked by TLC using mixed eluents n-hexane: ethyl acetate (4:1). The products of the study were powder with the appropriate weight range and yield of the reaction time (3 hours, 5 hours and 7 hours) was 0.16 g: 5.387%, 0.48 grams: 16.162% and 0.43 grams: 14.478%. the optimum time for this reaction was 5 hours. Key words: condensation, vanillin, p-nitroacetophenone, acid catalyst